DEVELOPMENTS OF POLYHEDRA USING OBLIQUE COORDINATES - Akiyama, J.; Nara, C. (Journal of the Indonesian Mathematical Society, 2007)
This paper is an exposition of the results in the paper entitled "Convex Development of a Regular Tetrahedron" by J. Akiyama, et. al. [1]. We fill in the detail which have been omitted in the paper. We determine all convex developments of a regular tetrahedron V using a tiling generated by V and we arrive at conditions for convex polygons to be convex develpments of V . Moreover, we identify all convex polyhedra whose convex developments can be determined by the method used for V .